Antimicrobial Activity of Seeds of Abrus precatorius Linn - Sreeramulu, J.; Raveendra Reddy, J.; Padmanabha Reddy, Y.; Geethavani, M. (Asian Journal of Chemistry, 2010)
In vitro studies of seeds of Abrus precatorius Linn were carried out, which includes determination of antimicrobial activity by different methods like cylindrical plate method and turbidimetric method. Determination of antibacterial activity by using the following strains of gram positive bacteria (Staphylococcus aureus and Bacillus subtilis) and gram negative (Escherichia coli and Salmonella typhi). In addition to this antifungal activity is also carried out by using the following strains of Candida albicans, Cryptococcus neoformans by using sabourand dextrose broth.